Clinical and school-based intervention strategies for youth obesity prevention: A systematic review - Caron, Théo; Bernard, Paquito; Gadais, Tegwen (Frontiers in Sports and Active Living, 2023)
Introduction In the last couple of decades, numerous intervention strategies (ISs) have been formulated in school/community or clinical sectors using physical activity (PA) in order to prevent youth obesity because they have been highly effective in addressing this issue. These two sectors have revealed some interesting information in terms of efficient results and best practice mechanisms, but comparisons between them to learn about their functioning have been rare. Methods Therefore, the aim of this systematic review was to analyze and synthesize PA ISs from school/community or clinical domains for the period 2013-2017, in French or English, targeting youths aged 5-19 years old through primary, secondary, and tertiary prevention. Results In total, 68 full articles were reserved for data extraction and synthesis and 617 were excluded because they did not meet eligibility criteria (61 of 68 were kept for the final analysis). The results identified a number of differences between the studies of the various IS sectors and also a third type of IS, mixed sector. Mixed ISs (clinical and school-community) have a special advantage because they can benefit from the strengths of both school/community-based and clinical-based ISs. Mixed ISs showed the most promising results. This review also highlighted the differences between sectors and their ISs in terms of intervention teams, prevention objectives, duration, materials, and efficiency. Conclusion Future studies should focus on establishing a prevention program in a given geographical area involving all stakeholders with their respective skills/knowledge, in the area of decision-making and in the development of ISs, to ensure that the program is the most efficient and best adapted to its environment.